782 Rhizarthrosis in banknote processing workers: a retrospective cohort study. (24th April 2018) - Verrijdt, G; De Landtsheer, A; Mellen, A-M; Godderis, L
Abstract : Introduction: Rhizarthrosis is a common condition affecting 10% to 30% of the population over the age of 60. Whether or not it is an occupational disease has been the subject of debate as epidemiological studies on the correlation between physical stress and the presence of rhizarthrosis have shown conflicting results. A cluster of cases among banknote processing workers was reported by the OHP to the Federal Agency for Occupational Risks for evaluation Methods: We have set up a retrospective cohort study covering195 employees currently or previously involved in the manual or automated processing of banknotes. Each participant's job history was carefully reconstructed and the number of months holding certain job titles determined. Each participant was clinically and radiologically examined for the presence of rhizarthrosis in both hands, scored by a combination of clinical and radiological criteria and related to exposure. Results: The prevalence of rhizarthrosis was 27% in female participants (mean age: 52.3 y±4.4 y) and 17% in male participants (mean age: 53.2±5.8 y). The odds ratio for rhizarthrosis after 10 years' full-time overall exposure was significantly higher (OR10y: 1.53 (1.03–2.28)). Surprisingly, one particular job, 'manual counting', described by participants as highly straining and severely taxing on the thumbs, has not shown any significantly higher prevalence of rhizarthrosis. Conclusion: Our study has confirmed the correlation between the presence of rhizarthrosis and age, gender and manual repetitive work. We found a significantly higher risk for banknote processing in general but not for one particular job ('manual counting'), although considered by participants as a strenuous effort for the thumbs. Discussion: This is the first study on the risk of developing rhizarthrosis in banknote processing workers. The result indicates they are at greater risk and calls for adequate occupational health monitoring to prevent irreversible damage to the CMC-1 joint.